Outbreak of Rift Valley Fever in Mauritania, 2022 - Nounengulie Kire; Michelle Lalrinsiami; M.C.Rajkumar; Arunpathy.P (University of New South Wales, 2023)
Rift valley fever (RVF) is a viral zoonosis endemic to Africa and Arabian Peninsula, that primarily affects animals but can also cause illness in humans. The Rift valley fever virus belongs to the Bunyaviridae family and is transmitted primarily by the Aedes and Culex genera. In Humans, transmission can also occur through contact with blood, body fluids, or tissues and ingesting unpasteurised or uncooked milk of infected animals. The disease symptoms range from mild fever and flu-like symptoms to severe hemorrhagic fever, encephalitis, and death. This watching brief describes the outbreak of RVF in Mauritania in 2022. The first case reported on 25th August, was a 25-year-old male, an animal breeder from Tintane district, Hodh El Gharbi wilaya. As of 17 October 2022, a total of 47 confirmed cases including 23 deaths (CFR 49%)-mostly among animal breeders- have been reported from nine of Mauritania's 15 wilayas, with a sex ratio of M:Fcases= 4.4:1 and median age of 22 years. There are currently no vaccines available for humans and treatment is only symptomatic. Prevention is by avoiding contact with blood & body fluids or tissues of infected animals, unsafe animal products and protection from mosquitoes. To prevent future outbreaks there is the need to promote safer animal husbandry and slaughter practices, strengthening of existing surveillance systems, implementation of vector control activities and restriction of movement of livestock from infected to uninfected areas.